Philadelphia chromosome-negative myeloproliferative chronic neoplasms: is clonal hematopoiesis the main determinant of autoimmune and cardio-vascular manifestations? - Giovanni Fulvio; Giovanni Fulvio; Chiara Baldini; Marta Mosca; Antonello di Paolo; Guido Bocci; Giuseppe Alberto Palumbo; Emma Cacciola; Paola Migliorini; Rossella Cacciola; Sara Galimberti (Frontiers in Medicine, 2023)
In this article, we reviewed the possible mechanisms linking the clonal hematopoiesis of indeterminate potential (CHIP) to chronic myeloproliferative neoplasms (MPNs), autoimmune diseases (ADs), and cardiovascular diseases (CADs). CHIP is characterized by the presence of clonal mutations with an allelic frequency >2% in the peripheral blood without dysplasia, overt hematological neoplasms, or abnormalities in blood cell count. The prevalence may reach 20% of elderly healthy individuals and is considered a risk factor for myelodysplastic neoplasms and acute leukemia. In MPNs, CHIP is often associated with mutations such as JAK2V617F or DNMT3A, TET2, or ASXL1, which exhibit a 12.1- and 1.7–2-fold increase in CADs. Specifically, JAK2-mutated cells produce excessive cytokines and reactive oxygen species, leading to proinflammatory modifications in the bone marrow microenvironment. Consequently, the likelihood of experiencing thrombosis is influenced by the variant allele frequency (VAF) of the JAK2V617F mutation, which also appears to be correlated with anti-endothelial cell antibodies that sustain thrombosis. However, DNMT3A mutations induce pro-inflammatory T-cell polarization and activate the inflammasome complex, while TET2 downregulation leads to endothelial cell autophagy and inflammatory factor upregulation. As a result, in patients with TET2 and DNMT3A-related CHIP, the inflammasome hyperactivation represents a potential cause of CADs. CHIP also occurs in patients with large and small vessel vasculitis, while ADs are more frequently associated with MPNs. In these diseases, monocytes and neutrophils play a key role in the formation of neutrophil extracellular trap (NET) as well as anti-endothelial cell antibodies, resulting in a final procoagulant effect. ADs, such as systemic lupus erythematosus, psoriasis, and arthritis, are also characterized by an overexpression of the Rho-associated coiled-coil containing protein kinase 2 (ROCK2), a serine/threonine kinase that can hyperactivate the JAK-STAT pathway. Interestingly, hyperactivation of ROCK2 has also been observed in myeloid malignancies, where it promotes the growth and survival of leukemic cells. In summary, the presence of CHIP, with or without neoplasia, can be associated with autoimmune manifestations and thrombosis. In the presence of these manifestations, it is necessary to consider a “disease-modifying therapy” that may either reduce the clonal burden or inhibit the clonally activated JAK pathway.